A finite element study on the effects of thickness and material nonlinearity on the equilibrium path of axially loaded circular cylindrical shells. (15th February 2023) - Adorno, Ruben; Palazotto, Anthony N.
Highlights: Equilibrium paths are simulated for shells of thicknesses: 1E−3m to 1E−6m. Nonlinear material effects are presented in association to shell thickness. Solutions show classical buckling load predictors can underestimate collapse. Finite element mesh size and yield limit dependencies are also discussed. Abstract: Research has been carried out in recent years dealing with Lighter than Air Structures (LTAS), in which the innermost volume is taken to be a vacuum. Variations of a thin membrane over a frame were considered in order for such structures to have buoyancy potential while being capable of sustaining atmospheric pressures. The need for extremely thin membranes became evident as a result of the weight constraint The potential for the development of a viscoplastic stress field and instability led to the study of a classical problem: the instability of circular cylindrical shells under compressive loading. Thus, in order to obtain information related to the nonlinear geometric and material effects that can eventually be used in the LTAS, this study focused on what increasingly smaller membrane thicknesses and changes in the modulus can have on the equilibrium path of circular cylindrical shells. Considering shell thicknesses from 1E−3 to 1E−6m and using the Johnson-Cook constitutive relationship, results show that (1) the equilibrium path is highly dependent on shell thickness, and (2) inelastic strains drive path deviations and distinct post-collapse shapes. Furthermore, a reduction in the yield stress can result in plasticity before collapse, effectively changing the path of equilibrium and the post-collapse shape. Solutions were found using SIMULIA® Abaqus finite element (FE) software. At the present time these membrane thicknesses and material properties are not available. It is felt that, with the advancement of material science, they will become available in the immediate future.